A Christmas carol - Dickens, Charles, 1812-1870 (Boston, Mass : Thomson Heinle, 2005)
A miser larns the true meaning of christmas when three ghostly visitors review his past and foretell his future
Title from container
Keywords: Scrooge, Ebenezer (Fictitious character) -- Fiction; Poor families -- Fiction; Sick children -- Fiction; Misers -- Fiction